Exploring the effect of teacher autonomy support on Chinese EFL undergraduates’ academic English speaking performance through the mediation of basic psychological needs and classroom engagement - Wang, Yanning; Luo, Weihua; Liao, Xian; Zhao, Pengfei (Frontiers in Psychology, 2024)
The capacity to speak English for academic purposes is a pivotal facet of language education and assessment. Despite the substantial research approving the significant role of teachers in L2 learning, it remains unclear how exactly teachers’ support for students’ learning autonomy influences EFL learners’ academic English speaking performance. To address this primary concern, this study drew ground from the Self-System Model of Motivational Development (SSMMD) and adopted a mixed-method approach to examine teacher autonomy support’s direct and indirect effects on Chinese EFL undergraduates’ academic English speaking performance through the mediation of basic psychological needs and classroom engagement. 247 first-year university students participating in academic English speaking courses were recruited in this study. The quantitative results of the questionnaire indicated that students’ perceived teacher support for autonomy directly predicted English speaking performance, and it also indirectly influenced students’ speaking performance via the mediation of classroom engagement and basic psychological needs. Students’ responses in the semi-conductive interview further verified the positive effect of teacher autonomy support on academic English speaking development in the classroom. Pedagogical implications were also discussed based on the findings.